Снerenkov radiation of the laser pulse in a dielectric waveguide - Balakirev, V.A.; Onishchenko, I.N. (Вопросы атомной науки и техники, 2018)
Theoretical studies of the excitation of the Cherenkov radiation by a superluminal laser pulse in a dielectric
waveguide, similar to the radiation of an electron moving uniformly in a slowing-down medium with a
superluminal velocity, are presented. The nonlinear polarization of the medium caused by the ponderomotive force
of a laser pulse is obtained. The structure of excited fields, including wakefields, is found. Frequency dispersion of
the dielectric permittivity is considered to provide superluminal group velocity of the laser pulse. Представлено теоретичні дослідження збудження черенковського випромінювання надсвітловим
лазерним імпульсом у діелектричному хвилеводі, аналогічного випромінюванню електрона, що рівномірно
рухається в уповільнюючому середовищі з надсвітловою швидкістю. Отримана нелінійна поляризація
середовища, викликана пондеромоторною силою лазерного імпульсу. Знайдена структура збуджуваних
полів, в тому числі кільватерних. Розглянута частотна дисперсія діелектричної проникності, що забезпечує
надсвітлову групову швидкість лазерного імпульсу. Представлены теоретические исследования возбуждения черенковского излучения сверхсветовым
лазерным импульсом в диэлектрической среде, аналогичного излучению электрона, равномерно
движущегося в замедляющей среде со сверхсветовой скоростью. Получена нелинейная поляризация среды,
вызванная пондеромоторной силой лазерного импульса. Найдена структура возбуждаемых полей, в том
числе кильватерных. Рассмотрена частотная дисперсия диэлектрической проницаемости, обеспечивающая
сверхсветовую групповую скорость лазерного импульса.